Enantioselective Copper‐Catalyzed Intermolecular Amino‐ and Azidocyanation of Alkenes in a Radical Process. Issue 8 (23rd January 2017) - Wang, Dinghai; Wang, Fei; Chen, Pinghong; Lin, Zhenyang; Liu, Guosheng
Abstract: Asymmetric copper‐catalyzed intermolecular amino‐ and azidocyanation reactions of alkenes have been developed that proceed via a radical process in which a key benzylic radical intermediate is enantioselectively trapped by a chiral Box/Cu II cyanide complex. A variety of enantiomerically enriched β‐amino/azido alkylnitriles were efficiently synthesized. The β‐azido alkylnitriles could be converted into a series of highly valuable optically active amine‐based building blocks and bioactive compounds. Abstract : A radical process is involved in the asymmetric copper‐catalyzed intermolecular amino‐ and azidocyanation of alkenes developed herein. A variety of enantiomerically enriched β‐amino/azido alkylnitriles were efficiently synthesized. The azidocyanation products were further converted into a series of optically active building blocks and bioactive compounds.